The D-NET Software Toolkit: A Framework for the Realization, Maintenance, and Operation of Aggregative Infrastructures. Issue 4 (19th August 2014) - Manghi, Paolo; Artini, Michele; Atzori, Claudio; Bardi, Alessia; Mannocci, Andrea; La Bruzzo, Sandro; Candela, Leonardo; Castelli, Donatella; Pagano, Pasquale
Abstract : Purpose: This paper presents the architectural principles and the services of the D-NET Software Toolkit. D-NET is a framework where designers and developers find the tools for constructing and operating aggregative infrastructures (systems for aggregating data sources with heterogeneous data models and technologies) in a cost-effective way. Designers and developers can select from a variety of D-NET data management services, can configure them to handle data according to given data models, and can construct autonomic workflows to obtain personalized aggregative infrastructures. Design/methodology/approach: The paper provides a definition of aggregative infrastructures, sketching architecture and components, as inspired by real-case examples. It then describes the limits of current solutions, which find their lacks in the realization and maintenance costs of such complex software. Finally, it proposes D-NET as an optimal solution for designers and developers willing to realize aggregative infrastructures. The D-NET architecture and services are presented, drawing a parallel with the ones of aggregative infrastructures. Finally, real-cases of D-NET are presented, to show-case the statement above. Findings: The D-NET software toolkit is a general-purpose service-oriented framework where designers can construct customised, robust, scalable, autonomic aggregative infrastructures in a cost-effective way. D-NET is today adopted by several EC projects, national consortia and communities to create customised infrastructures under diverse application domains, and other organisations are enquiring for or are experimenting its adoption. Its customisability and extendibility make D-NET a suitable candidate for creating aggregative infrastructures mediating between different scientific domains and therefore supporting multi-disciplinary research. Originality/value: D-NET is the first general-purpose framework of this kind. Other solutions are available in the literature but focus on specific use-cases and therefore suffer from the limited re-use in different contexts. Due to its maturity, D-NET can also be used by third-party organizations, not necessarily involved in the software design and maintenance.